State capacity, stakeholder buy-in, and collective action problems the budget allocation case. - Fabella, R. V.
Weak state capacity can lead to poor economic performance owing to an inability to solve collective action problems associated with lumpy but highly productive infrastructure projects. We formulate a stakeholder buy-in game where two players (regions) must unanimously approve a lumpy infrastructure program in which one region first gets the total budget in period one to finance a lumpy and productive project and the other region gets all the budget generated in period two. The program involves the state undertaking several tax-andtransfer steps in the implementation phase. Both would be better off if the program succeeds. But weak capacity is reflected in the probability that the state fails to deliver at each step. If either player rejects the program, the default allocation is Òdivideby- NÓ, where each player gets an Nth part of the given budget, which can finance only small and less productive projects. When state capacity exceeds a certain threshold, unanimous approval is a unique evolutionarily stable strategy. If not, the Òdivide-by-NÓ rule dominates. A higher return on lumpy projects reduces the hurdle probability and improves the likelihood of stakeholder buy-in. A higher degree of myopia among the players has the opposite effect.